A study on theory of Iceberg in “The Old Man and the Sea” by Earnest Hemingway. M.A Thesis Linguistics: 60 22 15 - Hán, Thị Bích Ngọc (University of Languages and International Studies, 2017)
The study firstly aimed at giving some certain information about ‘The Old Man and the Sea”, the last major work published in Ernest Hemingway’s life. Secondly, Hemingway’s distinctive writing style with the Iceberg Theory was thoroughly discussed, providin (...)